Optimasi Pertumbuhan Puyuh (Coturnix coturnix japonica L.) Hasil Pemeliharaan dengan Cahaya Monokromatik - Kasiyati, Kasiyati; Silalahi, Adonia Benedicta; Permatasari, Intan (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2011)
Light is one of exogenous factor that influence on quail growth. The objective of the research was optimize the quail growth  used to the  monochromatic light as source artificial light. Two hundred and fourty female quails (Coturnix coturnix japonica) were divided into eight treatments of lights, with thirty quails in each treatments.  The treatments were red (P11 and P12), green (P21 and P22), and blue (P31 and P32) lights with intensities of  15 and 25 lux. Control  treatment used yellow incandescent bulb of 15 (P01) and 25 (P02) watt. The red, green, and blue lights were provided by light emitting diodes (LED). All  lights treatment  were given  for 14 h daily,  started from 17.00 to 07.00 for six weeks. The result showed that quails exposed to monochromatic light significant (P<005)  in the body weight, the weight of pectoral muscle, and the length of tibial bone, but feed consumption decreased, and normal hemoglobin concentration. Green and blue light could be used to optimize the quail growth. Key word: monochromatic light, growth, hemoglobin concentration, quail